2019
DOI: 10.1111/resp.13504
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary artery enlargement predicts poor outcome during acute exacerbations of fibrotic interstitial lung disease

Abstract: Background and objective: In fibrotic interstitial lung disease (f-ILD), pulmonary artery diameter to ascending aorta diameter ratio (PA/A) ≥ 1 during the stable stage is associated with worse outcomes; however, the effect of acute exacerbation (AE) on the PA/A is unknown. Methods: Patients with a diagnosis of AE of f-ILD and with a computed tomography (CT) scan performed during stable period to confirm background fibrosis, as well as a CT scan at admission, were included. The pulmonary arterial diameter, asce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Second, Kogo et al . explored the prognostic significance of enlargement of the pulmonary artery, quantified as the pulmonary artery/aorta (PA/A) ratio, in acute exacerbations of fibrotic interstitial lung disease (fILD) . The authors found that a PA/A ratio > 1.0 was associated with increased 90‐day mortality before and after adjustment for a number of factors (FVC reduction prior to the acute exacerbation age, AE‐fILD severity and type of fILD).…”
mentioning
confidence: 99%
“…Second, Kogo et al . explored the prognostic significance of enlargement of the pulmonary artery, quantified as the pulmonary artery/aorta (PA/A) ratio, in acute exacerbations of fibrotic interstitial lung disease (fILD) . The authors found that a PA/A ratio > 1.0 was associated with increased 90‐day mortality before and after adjustment for a number of factors (FVC reduction prior to the acute exacerbation age, AE‐fILD severity and type of fILD).…”
mentioning
confidence: 99%
“…73 Kogo et al use the ratio of the pulmonary artery to aorta to prognosticate and report that a ratio of ≥1 predicts a greater risk of mortality associated with acute exacerbations. 74…”
Section: Acute Exacerbations Key Pointsmentioning
confidence: 99%
“…Enlargement of the pulmonary arteries as detected by contrast‐enhanced computed tomography pulmonary angiography (CTPA) provides prognostic information in patients with various forms of cardiopulmonary disease. Enlargement of the pulmonary artery diameter (PAd) or increased ratio of the PAd to aorta diameter (PA:AA) has been associated with increased mortality in patients with chronic obstructive pulmonary disease (COPD), 1 , 2 interstitial lung disease, 3 , 4 , 5 pulmonary arterial hypertension (PAH), 6 , 7 chronic thromboembolic pulmonary hypertension (CTEPH), 7 , 8 chronic systolic heart failure, 9 and severe COVID‐19 infection. 10 This is not surprising, as pulmonary artery enlargement on CTPA has been shown to correlate with other better defined assessments of pulmonary hypertension, including echocardiography and right heart catheterization, 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 and the presence of pulmonary hypertension is associated with a poor prognosis in many of these conditions.…”
Section: Introductionmentioning
confidence: 99%